"Whiteness" and natural resource management: let's talk about race baby, let's talk about sovereignty!. (26th October 2019) - Searle, Tania; Muller, Samantha
Abstract: Issues of race and sovereignty are embedded in every cross‐cultural collaboration in natural resource management (NRM). This article aims to bring these issues to the forefront by incorporating the term whiteness. Whiteness enables a critique of the privileging of Western sovereignty and the so‐called objective and universal value of Western science. By reversing the gaze away from the colonised Other and onto systems descended from colonial authority and its inheritors, whiteness identifies how race privilege works. A critical whiteness lens provides an analytical and practical tool for decolonising NRM. We provide a case study of the South Australian Department of Environment and Water to consider how NRM professionals reproduce and deconstruct whiteness in nuanced ways, where (a) participants are defeated by Western sovereignty when whiteness is seen as normal or as the only way; (b) the privilege of Western sovereignty begins to be unsettled; and (c) the gaze is reversed. Thus, Western sovereignty is problematized, and solutions to persistent problems are found in collaboration. We argue that reversing the gaze is a process that opens spaces to co‐develop context specific solutions with Indigenous nations that decolonise cross‐cultural engagement in NRM and respect Indigenous sovereignty.